Determinant of Employee’s Turnover Intention: The Analysis of Career Development, Organization Justice, and Trust in Organization - Ari Apriani; Siti Annisa Wahdiniawati; Esti Liana; Hartono (PT FORMOSA CENDEKIA GLOBAL, 2023)
An organization consists of a group of people who are formally assigned roles to work together to achieve organizational goals. Meanwhile, a manager is a person who is given the responsibility to achieve corporate goals by making various efforts for human existence in the organization. Therefore, given the importance of the human role in today's competitive environment, it is not surprising that the position of employees as human capital is the most important factor as a crucial component of the development of an organization. The objective of this article review analysis is to discover the factors that can influence employees' intention to leave. The method of this analysis is the qualitative method, in which the literature of previous articles up to 21 articles is reviewed. The results show that career advancement, organizational fairness and organizational trust. These findings can provide a reference for business leaders to identify factors that may influence turnover intention